Vocational Interests of Juvenile Delinquents in the Institutions of Juvenile Education and Rehabilitation in Jordan - Al-Halalat, Khalil (Jordan Journal of Social Sciences, 2021)
The study aims to identify the vocational interests of juvenile delinquents in the institutions of juvenile education and rehabilitation in Jordan, and to identify if there are statistically significant differences in the professional tendencies of juvenile delinquents and some of their demographic characteristics. The study used the social survey method, and the study population consisted of all arrested and convicted juveniles present in the institutions of juvenile education and rehabilitation in Jordan. The study was conducted using the comprehensive enumeration method during the period of conducting the study, and the number of respondents reached (112) juveniles. Among the most prominent results of the study regarding the demographic characteristics is that the highest percentage of juveniles, at a rate of (35.71%), were for juveniles arrested in the Rusaifah juvenile education institution, and the highest percentage of juveniles' ages came between 16-18 years, representing (73.21%), and the highest percentage of juveniles whose educational level was higher Secondary (28.57%). The study shows that the highest charges were theft, at a rate of (33.4%), and the lowest was the charge of murder (11.61%), and that the percentage of juveniles sentenced (30.36%) and those arrested were (69.64%). In vocational interests, the results show that the highest paragraph in the artistic environment was "I would like to be a photographer" and it came in the average of (3.22), and the arithmetic mean of the dimension as a whole was (2.87), and the highest paragraph in the real environment came as "I would like to be a farmer" and it came in the average of (3.12). The arithmetic mean of the dimension as a whole was (3.94), and in the area of social environment, the highest paragraph in the vocational interests of juveniles was "I want to be a religious preacher" in arithmetic mean (3.37) and the field as a whole came with an arithmetic mean of (3.10), A paragraph on the Vocational Interests of juveniles in the adventurous environment field was "I would like to be a criminal investigator" and "I would like to be a judge" in the average of (3.47) for both , and the arithmetic mean for the field as a whole was (3.10). In the traditional environment field, the highest paragraph came in the vocational interests of juveniles, which were “I tend to be a bank auditor” in the average of (3.12), and the field as a whole came in the average of (2.91), and the mental environment field came as the highest paragraph in the vocational interests of juveniles “I tend to be a pharmacist "With an arithmetic mean of (3.44), and the arithmetic mean of the domain as a whole was (3.09). As for the ranking of the fields of occupational orientation for juvenile delinquents, the highest field came in the adventurous environment and the lowest was the realistic environment. The study shows that there are no statistically significant differences in the vocational interests of the juveniles in the artistic environment, the realistic environment, the traditional environment, and the adventurous environment due to age. However, in the social environment and the mental environment, there are statistically significant differences in the vocational interests of juveniles due to age, there are statistically significant differences in the vocational interests of juveniles in the technical environment and the real environment due to the educational level, and there are no statistically significant differences in the rest of the environments, there are significant differences statistically in the vocational interests of juveniles in the artistic environment in terms of their staying in school. As for the rest of the environments for the vocational Interests of juvenile delinquents, it was not statistically significant. There are no statistically significant differences in the occupational tendencies in the six environmental domains of juvenile delinquents attributable to the nature of the juvenile’s work. Statistically significant differences in occupational preferences in the six environmental domains of juvenile delinquents attributed to the nature of the father's work.